Security, strategy, and military dynamics in South China Sea : cross-national perspectives - Houlden, Gordon; Romaniuk, Scott Nicholas; Hong, Nong (Bristol University Press, 2021)
Bringing together international experts, this collection provides fresh perspectives on geopolitical concerns in the South China Sea. It is an accessible, even-handed examination of current and future rivalries and challenges in one of the most strategically important and militarized maritime regions of the world.